Evaluation of confirmatory data following the Article 12 MRL review and modification of the existing maximum residue levels for metazachlor in various commodities. (15th October 2019) - ,; Anastassiadou, Maria; Brancato, Alba; Carrasco Cabrera, Luis; Greco, Luna; Jarrah, Samira; Kazocina, Aija; Leuschner, Renata; Magrans, Jose Oriol; Miron, Ileana; Nave, Stefanie; Pedersen, Ragnor; et al.
Abstract: The applicant BASF SE submitted a request to the competent national authority in the Netherlands to evaluate the confirmatory data that were identified for active substance metazachlor in the framework of the review of maximum residue levels (MRLs) under Article 12 of Regulation (EC) No 396/2005 as not available. The data gaps identified during the MRL review were satisfactorily addressed for flowering brassica, head cabbages, kales and kohlrabies. The applicant no longer supported the uses on radishes, turnips, horseradishes and swedes assessed during the MRL review. In addition, in accordance with Article 6 of Regulation (EC) No 396/2005, the applicant submitted a request to modify the existing MRLs in turnips, swedes, horseradishes and leeks to reflect intended new uses. Nevertheless, the residue data submitted were not fully compliant with the currently applicable data requirements. For turnips, horseradishes and swedes, the applicant and the Netherlands requested EFSA to present the data and the deficiencies identified to allow risk managers to take an informed decision on the appropriate MRLs. A change of the existing MRLs for liver of swine and ruminants resulting from the authorised and intended uses of metazachlor is also proposed. EFSA updated the most recent consumer risk assessment for metazachlor and concluded that the long‐term and short‐term dietary intake is unlikely to present a risk to consumer health.